2013
DOI: 10.3390/s131217332
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Delayed Fluorescence from Photosystem II

Abstract: While photosystem II (PSII) of plants utilizes light for photosynthesis, part of the absorbed energy may be reverted back and dissipated as long-term fluorescence (delayed fluorescence or DF). Because the generation of DF is coupled with the processes of forward photosynthetic activities, DF contains the information about plant physiological states and plant-environment interactions. This makes DF a potentially powerful biosensing mechanism to measure plant photosynthetic activities and environmental condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Leaves of different plants have different diffusion and binding rates for a given herbicide, which allows the selection of optimal plant leaves to improve the performance of the developed method for the herbicide measurement in real applications. DF from PSII can be potentially used to sense photosynthesis rate, herbicide, metal pollution, drought stress, plant senescence, nutrients, chilling stress, heat stress, salt stress, acid rain, and plant circadian (Guo and Tan, 2013b). The research of using DF as a biosensor in the literature was conducted in time domain.…”
Section: Discussionmentioning
confidence: 99%
“…Leaves of different plants have different diffusion and binding rates for a given herbicide, which allows the selection of optimal plant leaves to improve the performance of the developed method for the herbicide measurement in real applications. DF from PSII can be potentially used to sense photosynthesis rate, herbicide, metal pollution, drought stress, plant senescence, nutrients, chilling stress, heat stress, salt stress, acid rain, and plant circadian (Guo and Tan, 2013b). The research of using DF as a biosensor in the literature was conducted in time domain.…”
Section: Discussionmentioning
confidence: 99%
“…BIG was identified originally as a light signaling regulator (Li et al, 1994) and later was shown to also control multiple hormone signaling pathways (Kanyuka et al, 2003), including auxin transport (Guo and Tan, 2013), and recently was implicated in CO 2 -induced stomatal closure (He et al, 2018). The precise biochemical functions of BIG are unknown, but mutations in Pushover and knockout or down-regulation of UBR4 also produce pleiotropic phenotypes (Richards et al, 1996;Sekelsky et al, 1999;Yager et al, 2001;Nakatani et al, 2005;Belzil et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This type of chlorophyll fluorescence thus has much longer life time and is named as delayed fluorescence. The intensity of delayed fluores-cence is several orders of magnitude weaker than that of PF (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 89%
“…Chlorophylls in Photosystem I (PSI) may produce ChlF also, but the emission from PSI only accounts for a small fraction of the total measured ChlF and is not sensitive to environmental changes (13). Applications of delayed fluorescence are summarized in (10) and thus not discussed here. This article, therefore, will focus on prompt ChlF from PSII.…”
Section: Introductionmentioning
confidence: 99%